What is sexual wellbeing and why does it matter for public health? - Mitchell, Kirstin R (Lancet Public Health, 2021)
Sexual health has provided a guiding framework for addressing sexuality in public health for several decades. Although the WHO definition of sexual health is revolutionary in acknowledging positive sexuality, public health approaches remain focused on risk and adverse outcomes. The long-standing conflation of sexual health and sexual wellbeing has affected our ability to address everyday sexual issues. This Viewpoint provides a way forward to resolve this impasse. We propose sexual wellbeing as a distinct and revolutionary concept that can be operationalised as a seven-domain model. We situate sexual wellbeing alongside sexual health, sexual justice, and sexual pleasure as one of four pillars of public health enquiry. We argue that sexual wellbeing is imperative to public health as a marker of health equity, a meaningful population indicator of wellbeing, a means to capture population trends distinct from sexual health, and an opportunity to refocus the ethics, form, and practices of public health.